Philomena de Chretien de Troyes: Métamorphose d’une métamorphose au temps du roman - Sylvia Roustant (Carnets)
This work of Chrétien de Troyes has often been read, studied, within l'Ovide moralisé (fourteenth century), where it has been discovered, but which is posterior to its writing (late twelfth century). We therefore have to place this work in context: the advent of roman, new kind of genre using a new kind of writing language. Thus Philomena is primarily the story of a linguistic metamorphosis. Latin previously used in written works, is giving way to the Romance language. We also have to place Philomena among the other pieces of the work of Chrétien de Troyes, showing in particular it contains the germ of the main themes and questions of Chrétien's works. Philomena is also the story of a cultural metamorphosis since the author has rewritten this myth as a cons-model of courtesy. To consider Philomena as an essential moment in terms of language and culture, we will rely primarily on the handling of the time, really different in this work of Chrétien de Troyes.